Pengaruh Permainan Edukatif di Luar Kelas pada Motorik Kasar Siswa Autis di TK Inklusi - Angger Timansah; Arifah Nurhadiyati (Journal on Education, 2023)
This research was used to improve gross motor development in autistic children at the Star Kids Jember Inclusion Kindergarten through educational games outside the classroom. The subjects of this study amounted to 6 people. Data collection techniques from this study used observation, interviews and documentation. Non-parametric statistics are a type of Wilcoxon test which is also applied in this study. Research on a group taken in trials, not compared and samples not randomly selected is the type of research used, quantitative data analysis in the form of mathematical numbers and data collection using research instruments is a type of pre-experimental research. Quantitative approach is used in this research. Due to the variety of information using research instruments, the examination of information is quantitative in nature as a purely numerical figure intended to test established speculations. The aftereffects of the review show that outdoor games have a huge effect on autistic children, especially gross motor skills. In outdoor games n gross engine improvement in autistic kids, it can be seen from the results of research from data processing using the Wilcoxon formula and obtained t value = 2.202, which means that the outcomes showed that there was a critical impact between outdoor games in autistic kids, especially gross coordinated movements in Jember Star Kids Inclusion school.